Exchange bias in ferrite hollow nanoparticles originated by complex internal magnetic structure - de Biasi, Emilio (2015)
Iron-oxide hollow nanospheres (HNS) may present unusual magnetic behavior as a consequence of their unique morphology. Here, we report the unusual magnetic behavior ofHNS that are 9 nmin diameter. The magnetic properties ofHNSoriginate in their complex magnetic structure, as evidenced by Mössbauer spectroscopy and magnetization measurements.Weobserve a bias in the hysteresis when measured at very low temperature in the field cooling protocol (10 kOe). In addition, dc (static) and ac (dynamic) magnetization measurements against temperature and applied field reveal a frustrated order of the system below 10 K. High-resolution transmission electron microscopy (HRTEM) studies reveal that theHNSare composed of small crystalline clusters of about 2 nmin diameter, which behave as individual magnetic entities. Micromagnetic simulations (using conjugate gradient in order to minimize the total energy of the system) reproduce the experimentally observed magnetic behavior. The model considers the hollow particles as constituted by small ordered clusters embedded in an antiferromagnetic environment (spins localized outside the clusters). In addition, the surface spins (in both inner and outer surfaces of theHNS) are affected by a local surface anisotropy. The strong effective magnetic anisotropy field of the clusters induces the bias observed when the system is cooled in the presence of a magnetic external field. This effect propagates through the exchange interaction into the entire particle.